Multicomponent Template Effects - Preparation of Highly Porous Polyaniline Nanorods Using Crude Lemon Juice and Its Application for Selective Detection of Catechol - Gautam V.; Singh K.P.; Yadav V.L. (My University, 2025)
This paper deals with the preparation and characterization of three different polyaniline samples, namely, PANI-HCl (synthesis in inorganic acid), PANI-Citric acid (synthesis in organic acid), and PANI-Lemon (synthesis in crude lemon juice-biological-derived acidic solution). PANI-Lemon is a low-density polymer with well-defined nanorod shape morphology (∼100 nm in diameter and ∼300-600 nm in length). Lemon juice manipulates the morphology of PANI because it has a lower pKa and the matrix molecules produce template-like effects. The distinct structure of PANI-Lemon was confirmed from microscopic and spectroscopic analysis. In the same protonating condition, the alignment of chains is the dominating factor which governs the conductivity of polyaniline. PANI-Lemon was successfully applied for the electrocatalytic detection of catechol. The selective interaction of PANI-Lemon with catechol leads to the generation of a new redox center. PANI-Lemon-modified carbon paste electrode exhibited high sensitivity (49.68 μA μM-1 cm-2), specificity, a wide linear range (from 5 μM to 100 mM), a low detection limit (2.1 μM), and less response time (2 s). On the basis of our results, we propose an eco-friendly concept "multicomponent template effects" to bring nanoscale morphological manipulation using a suitable natural extract. This concept could be equally implemented to synthetic polymers and other nanoparticles. © 2017 American Chemical Society.